Ingestion of designer supplements produced positive doping cases unexpected by the athletes - Parr, M. K.; Pokrywka, A.; Kwiatkowska, D.; Schänzer, W. (Biology of Sport, 2011)
Since the end of the last century, the sport community has been grappling with contamination and faking of dietary or nutritional supplements. Publication of the results of many studies on this problem has resulted in educational and informative actions on risk connected with consumption of unchecked products. As compared to the past, nowadays athletes have become incomparably more aware of the potential risk of a positive result in anti-doping tests as a consequence of consumption of contaminated dietary supplements. However, this problem is still topical, which is confirmed by regular reports, presented e.g. during the Cologne Workshops on Dope Analysis held annually in Germany. This paper presents a few doping cases caused by the use of supplements with doping substances by athletes, noted by two WADA accredited laboratories (Cologne and Warsaw). Still more education on the health and doping risks of dietary supplement products seems to be necessary for the protection of both athletes and the general public.